Photoelectric active iron-carbon nano composite material and preparation method thereof

By performing high-temperature and high-pressure treatment and catalytic treatment in the preparation device, the problem of insufficient bonding and photoelectric activity of iron-carbon nanocomposite elements is solved, and higher bonding and photoelectric activity are achieved, meeting the needs of material specifications.

CN119553163AInactive Publication Date: 2025-03-04GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411479473.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the process of preparing iron-carbon nanocomposites, the two elements of iron-carbon are not highly combined, and the material after forming is weak in photoelectric activity, which cannot meet the requirements of required material specifications.

Method used

A specific preparation device and process flow is adopted, including weighing units, mixing units, active units and molding units, and the carbon material with porous structure is decomposed by the precursor under high temperature and high pressure, and catalytic treatment is carried out in the active units to improve photoelectric activity.

Benefits of technology

The bonding and photoelectric activity of the two elements of iron and carbon are improved, the stability and performance of the material are enhanced, and the requirements of required material specifications are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553163A_ABST
    Figure CN119553163A_ABST
Patent Text Reader

Abstract

The invention discloses a photoelectric active iron-carbon nano composite material and a preparation method thereof, and relates to the technical field of composite material preparation, the photoelectric active iron-carbon nano composite material comprises 40-50 parts of iron salt, 50-60 parts of a carbon material, 5-10 parts of a cocatalyst and 1-5 parts of a precursor, the composite material is distributed and put in a preparation device, the preparation device comprises a weighing unit, a mixing unit, an active unit and a forming unit, and the mixing unit is connected with the forming unit. A weighing module and a proportioning module are arranged in the weighing unit; a sealing module, a temperature / pressure control module and a stirring module are arranged in the mixing unit; a catalysis module is arranged in the active unit; a mold module and a removal module are arranged in the forming unit, and the method comprises the steps that S1, raw materials are weighed, specifically, by using a weighing module in a weighing unit, ferric salt, a carbon material and a precursor with different components are taken out, and according to counting of a proportioning module, the ferric salt, the carbon material and the precursor are concentrated in the same container according to the proportion of 5: 4: 2;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite material preparation, in particular to a photoelectrically active iron-carbon nanocomposite material and a preparation method thereof. Background Art

[0002] Nanocomposites are made of a matrix such as resin, rubber, ceramic and metal as a continuous phase, and modifiers such as nano-sized metals, semiconductors, rigid particles and other inorganic particles, fibers, nano-carbon tubes, etc. as a dispersed phase. The modifiers are evenly dispersed in the matrix material through appropriate preparation methods to form a composite system containing nano-sized materials. This system of materials is called a nanocomposite material. Among them, iron-carbon nanocomposites need to be prepared in a specific environment.

[0003] At present, in the process of preparing iron-carbon nanocomposite materials, due to the influence of environmental factors, the degree of bonding between the two elements of iron and carbon is easily low, and the photoelectric activity of the surface of the material after molding is weak and cannot meet the requirements of the required material specifications. Summary of the invention

[0004] The object of the present invention is to provide a photoelectrically active iron-carbon nanocomposite material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] By adopting the above technical solution, an iron-carbon nanocomposite material with a higher degree of bonding between the two elements of iron and carbon and stronger photoelectric activity can be prepared.

[0006] In view of the above problems, the technical solution proposed by the present invention is: A photoelectrically active iron-carbon nanocomposite material is prepared by measuring and distributing raw materials, including 40-50 parts of iron salt, 50-60 parts of carbon material, 5-10 parts of promoter and 1-5 parts of precursor. The composite material is distributed in a preparation device, and the preparation device comprises a weighing unit, a mixing unit, an active unit and a molding unit. A weighing module and a proportioning module are arranged inside the weighing unit, a sealing module, a temperature / pressure control module and a stirring module are arranged inside the mixing unit; a catalytic module is arranged inside the active unit; and a mold module and a removal module are arranged inside the molding unit.

[0007] In another aspect, the present invention provides a method for preparing a photoelectrically active iron-carbon nanocomposite material, comprising the following steps: S1. Weighing raw materials: Using a weighing module in a weighing unit, take out different amounts of iron salt, carbon material and precursor respectively, and according to the counts of the proportioning module, collect them in the same container in a ratio of 5:4:2; S2, mixing reaction: the raw materials of step S1 are transferred to the sealing module in the mixing unit, and the temperature and pressure in the sealing module are regulated by adjusting the temperature / pressure control module, wherein the temperature is controlled at 500-800°C and the pressure is controlled at 1000-1500Pa, and in this space, the raw materials are mixed by the stirring module, and the stirring time is controlled at 1-2h; S3, surface treatment: after completing the stirring and mixing in step S2, the raw materials are transported to the active unit, and a co-catalyst is added to react in the catalytic module, and the outer surface of the composite material is activated. At the same time, the polarization is regulated by temperature, stress, and electric field factors to affect the separation of electron-hole pairs, thereby affecting the photocatalytic activity; S4, molding optimization: The activated composite materials are placed one by one into the mold module in the molding unit to be shaped, and the molded composite materials are placed into the removal module for machine inspection, and the composite materials that do not meet the specifications are removed.

[0008] As a preferred technical solution of the present invention, in step S1, the weighing module adopts an electronic scale, and the carbon material is set to be any one of carbon powder and carbon particles.

[0009] As a preferred technical solution of the present invention, in step S1, the proportioning module is set to be any one of a paper recording form and a digital recording form.

[0010] As a preferred technical solution of the present invention, in step S2, the sealing module adopts an electrode heating high-pressure tank, the temperature / pressure control module adopts an integrated numerical control device, and the control end of the integrated numerical control device is arranged on the outer wall of the electrode heating high-pressure tank.

[0011] As a preferred technical solution of the present invention, in step S2, the stirring module adopts a multi-axis stirrer, and the multi-axis stirrer is arranged inside the electrode heating high-pressure tank.

[0012] As a preferred technical solution of the present invention, in step S3, the co-catalyst is set to be either ZnO / g-C3N4 or TiO2 / g-C3N4.

[0013] As a preferred technical solution of the present invention, in step S4, the mold module adopts a multi-column-shaped mold base, and the inner wall of the multi-column-shaped mold base is provided with an anti-adhesion coating.

[0014] As a preferred technical solution of the present invention, in step S4, a conveyor and an infrared sorting machine are provided inside the removal module.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The photoelectrically active iron-carbon nanocomposite material prepared by the present invention not only improves the bonding degree of the two elements of iron and carbon, but also improves the photoelectric activity and stability of the composite material. The precursor is subjected to high temperature and high pressure, so that the precursor can be decomposed at high temperature to generate a carbon material with a porous structure. The pore structure provides an ideal place for the reduction and loading of iron salts, and the dispersibility and stability of nano iron particles can be improved by adjusting the ratio of iron salts and carbon materials, avoiding the reduction of their activity due to agglomeration. Secondly, the catalytic treatment in the active unit can accelerate the reaction of the catalyst, and the polarization is regulated by temperature, stress, electric field and external field factors to affect the separation of electron-hole pairs, thereby affecting the photocatalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A module block diagram for preparing a photoelectrically active iron-carbon nanocomposite material provided by the present invention; Figure 2 The present invention provides a flowchart of a method for preparing a photoelectrically active iron-carbon nanocomposite material. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] See also Figure 1-Figure 2 The present invention provides a technical solution: a photoelectrically active iron-carbon nanocomposite material, wherein the raw materials for preparation are distributed in a measured amount, including 40 parts of iron salt, 50 parts of carbon material, 5 parts of promoter and 1 part of precursor, wherein the composite material is distributed in a preparation device, and the preparation device includes a weighing unit, a mixing unit, an active unit and a molding unit, wherein a weighing module and a proportioning module are arranged inside the weighing unit, a sealing module, a temperature / pressure control module and a stirring module are arranged inside the mixing unit; a catalytic module is arranged inside the active unit; and a mold module and a removal module are arranged inside the molding unit.

[0019] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Embodiment 1 See also Figure 1-Figure 2 The present invention provides a technical solution: a method for preparing a photoelectrically active iron-carbon nanocomposite material, comprising the following steps: S1. Weighing raw materials: Using a weighing module in a weighing unit, take out different amounts of iron salt, carbon material and precursor respectively, and according to the counts of the proportioning module, collect them in the same container in a ratio of 5:4:2; S2, mixing reaction: the raw materials of step S1 are transferred to the sealing module in the mixing unit, and the temperature and pressure in the sealing module are regulated by adjusting the temperature / pressure control module, wherein the temperature is controlled at 500° C. and the pressure is controlled at 1000 Pa. In this space, the raw materials are mixed by the stirring module, and the stirring time is controlled at 1.5 h; S3, surface treatment: after completing the stirring and mixing in step S2, the raw materials are transported to the active unit, and a co-catalyst is added to react in the catalytic module, and the outer surface of the composite material is activated. At the same time, the polarization is regulated by temperature, stress, and electric field factors to affect the separation of electron-hole pairs, thereby affecting the photocatalytic activity; S4, molding optimization: The activated composite materials are placed one by one into the mold module in the molding unit to be shaped, and the molded composite materials are placed into the removal module for machine inspection, and the composite materials that do not meet the specifications are removed.

[0021] Wherein, in step S1, the weighing module adopts an electronic scale, and the carbon material is set as carbon powder.

[0022] Wherein, in step S1, the proportioning module is set as a paper record form.

[0023] Wherein, in step S2, the sealing module adopts an electrode heating high-pressure tank, the temperature / pressure control module adopts an integrated numerical control device, and the control end of the integrated numerical control device is arranged on the outer wall of the electrode heating high-pressure tank.

[0024] Wherein, in step S2, the stirring module adopts a multi-axis stirrer, and the multi-axis stirrer is arranged inside the electrode heating high-pressure tank.

[0025] Wherein, in step S3, the co-catalyst is set to ZnO / g-C3N4.

[0026] Wherein, in step S4, the mold module adopts a multi-column-shaped mold base, and the inner wall of the multi-column-shaped mold base is provided with an anti-adhesion coating.

[0027] Wherein, in step S4, a conveyor and an infrared sorting machine are provided inside the removal module.

[0028] Embodiment 2 The method steps are as shown in Example 1 Wherein, in step S1, the weighing module adopts an electronic scale, and the carbon material is set as carbon particles.

[0029] Wherein, in step S1, the proportioning module is set as a digital recording table.

[0030] Wherein, in step S2, the sealing module adopts an electrode heating high-pressure tank, the temperature / pressure control module adopts an integrated numerical control device, and the control end of the integrated numerical control device is arranged on the outer wall of the electrode heating high-pressure tank.

[0031] Wherein, in step S2, the stirring module adopts a multi-axis stirrer, and the multi-axis stirrer is arranged inside the electrode heating high-pressure tank.

[0032] Wherein, in step S3, the co-catalyst is set to TiO2 / g-C3N4.

[0033] Wherein, in step S4, the mold module adopts a multi-column-shaped mold base, and the inner wall of the multi-column-shaped mold base is provided with an anti-adhesion coating.

[0034] Wherein, in step S4, a conveyor and an infrared sorting machine are provided inside the removal module.

[0035] In summary, both embodiments can prepare an iron-carbon nanocomposite material with a higher degree of bonding between the two elements of iron and carbon and stronger photoelectric activity.

Claims

1. A photoelectrically active iron-carbon nanocomposite material, wherein the raw materials for preparation are measured and distributed, including 40-50 parts of iron salt, 50-60 parts of carbon material, 5-10 parts of promoter and 1-5 parts of precursor, wherein: The composite material is distributed in a preparation device, which includes a weighing unit, a mixing unit, an active unit and a molding unit. The weighing unit is provided with a weighing module and a proportioning module, the mixing unit is provided with a sealing module, a temperature / pressure control module and a stirring module; the active unit is provided with a catalytic module; the molding unit is provided with a mold module and a removal module.

2. A method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 1, characterized in that: The following steps are involved: S1. Weighing raw materials: Using a weighing module in a weighing unit, take out different amounts of iron salt, carbon material and precursor respectively, and according to the counts of the proportioning module, collect them in the same container in a ratio of 5:4:2; S2, mixing reaction: the raw materials of step S1 are transferred to the sealing module in the mixing unit, and the temperature and pressure in the sealing module are regulated by adjusting the temperature / pressure control module, wherein the temperature is controlled at 500-800°C and the pressure is controlled at 1000-1500Pa, and in this space, the raw materials are mixed by the stirring module, and the stirring time is controlled at 1-2h; S3, surface treatment: after completing the stirring and mixing in step S2, the raw materials are transported to the active unit, and a co-catalyst is added to react in the catalytic module, and the outer surface of the composite material is activated. At the same time, the polarization is regulated by temperature, stress, and electric field factors to affect the separation of electron-hole pairs, thereby affecting the photocatalytic activity; S4, molding optimization: The activated composite materials are placed one by one into the mold module in the molding unit to be shaped, and the molded composite materials are placed into the removal module for machine inspection, and the composite materials that do not meet the specifications are removed.

3. The method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 2, characterized in that: In step S1, the weighing module adopts an electronic scale, and the carbon material is set to be any one of carbon powder and carbon particles.

4. The method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 2, characterized in that: In step S1, the proportioning module is set to be either a paper recording form or a digital recording form.

5. The method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 2, characterized in that: In step S2, the sealing module adopts an electrode heating high-pressure tank, the temperature / pressure regulating module adopts an integrated numerical control device, and the control end of the integrated numerical control device is arranged on the outer wall of the electrode heating high-pressure tank.

6. The method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 5, characterized in that: In step S2, the stirring module uses a multi-axis stirrer, and the multi-axis stirrer is arranged inside the electrode heating high-pressure tank.

7. The method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 2, characterized in that: In step S3, the co-catalyst is set to be either ZnO / g-C3N4 or TiO2 / g-C3N4.

8. The method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 2, characterized in that: In step S4, the mold module adopts a multi-column-shaped mold base, and the inner wall of the multi-column-shaped mold base is provided with an anti-adhesion coating.

9. The method for preparing a photoelectrically active iron-carbon nanocomposite material according to claim 2, characterized in that: In step S4, a conveyor and an infrared sorting machine are provided inside the removal module.